Reputação das Autoridades Monetárias e Credibilidade das suas Políticas: uma Abordagem Pós-keynesiana - Sicsú, João (Estudos Econômicos (São Paulo), 2021)
According to Keynes and post keynesians, monetary policy is able to realize two important tasks: to reduce unemployment and to cut off inflation. However, the post keynesian instrumental of monetary policy does not have faced discussions on forward-looking expectations to authority’s monetary actions. This article shows up some situations where these expectations change the expected results of monetary policy or still can cancel its efficacy. One intends to incorporate lessons learned with the concepts of reputation and credibility developed by new classical economics.